"A sea of love" : the Atlantic correspondence of Francis and Mathilde Lieber, 1839-1845 - Schnurmann, Claudia; Lieber, Francis, 1800-1872; Lieber, Mathilde, 1805-1890 (Brill's specials in modern history ;, 2018)
"A Sea of Love presents 95 letters exchanged between Hamburg and Antebellum USA by the famous Berlin born scholar, encyclopedist, and knowledge broker Francis Lieber (1798-1872) and his wife, Hamburg born Mathilde in 1839-1845. Their letters offer rare insights in the privacy of marriage and family life, self perceptions, notions of surroundings, as well as mental settings of the spouses. Beyond genuine individual phenomena of their Atlantic emotions their epistles show ways and methods of international communication and networking. Their writings reflect general notions and ideas shared by well-educated citizens of an Atlantic Republic of Letters connected by culture, interests, and emotions"--